The Effect of Chemical Compositions and Beating Time on The Production of Cellulosic Packaging Materials (Pulp) Using Oil Palm Empty Fruit Bunch (Efb) - Nor Adiella, Mohd Kamarudin (2012)

(untitled)
In palm oil mill processing, the waste product from palm oil mill was identified consists of oil palm trunks (OPT), oil palm fronds (OPD), empty fruit bunches (EFB), palm pressed fibers (PPF) and palm kernel shells. Follow Prasertsan, during palm oil processing, more than 70% by weight of fresh fruit bunches were left over as a waste. Analysts estimate that processing of palm oil mill yield 17 million tones of empty fruit bunches per year. Researcher believed that empty fruit bunches has potential as packaging product since its content high cellulose. Due to high user of non-degradable packaging, government put the full effort to find the alternative ways to reduce the use of non-degradable packaging. Empty fruit bunches was see as an alternative to make degradable packaging product. In order to make packaging product from empty fruit bunch, soda antraquinone (soda AQ) and sodium hydroxide (NaOH) is used as chemical pulping because this chemical pulping will produce the better properties of pulp to make the packaging product. Sample of pulp was made at different soda composition and at different time of beating process in order to get optimum condition of properties of packaging product. After the best sample was selected, the standard physical testing was carried out. The study shows that beating effect and different composition of soda produces pulp at different fiber morphology, strength and packaging properties.